Fair Value Accounting: Enhanced Accuracy or Increased Market Volatility? - Marvin Franko; Mukhtaruddin Mukhtaruddin (AKUNTANSI 45, 2026)
Fair value accounting has become an important yet debated method for measuring financial performance, especially in the wake of significant economic downturns. This systematic literature review explores whether fair value accounting improves the precision of financial statements or contributes to fluctuations in the market. By analyzing 40 articles published from 2020 to 2025, predominantly from Scopus and ScienceDirect this review examines the dual characteristics of fair value measurements in current financial systems. The review consolidates theoretical frameworks, empirical findings, and practical implications across various industries, including banking, insurance, and real estate. The results indicate a complicated relationship: fair value accounting shows greater value accuracy and clarity in stable market environments, but it also heightens procyclical impacts and disparities in information during financial crises. This review concludes that the success of fair value accounting is contingent on the context, shaped by market conditions, regulatory environments, and the level of fair value measurements applied.